An integrative, holistic treatment approach for veterans with chronic traumatic brain injury and associated comorbidities: case report - Dieterich-Hartwell, Rebekka; Brodovsky, Janine; DeAlba, Kathryne; Rubin, Allison; McGuigan, Emily; Mehmel, Bindal M.; Sergeyenko, Yevgeniya (Frontiers in Psychiatry, 2025)
This case report of a veteran with a history of multiple traumatic brain injuries, posttraumatic stress, and chronic pain highlights the MossRehab Institute for Brain Health (MRIBH) model of care: a collaborative, interdisciplinary, intensive outpatient treatment program. Unique to this case was the severity of symptomatology and the concerted engagement by the clinicians, who fully tailored and adjusted their approaches based on team rounds and daily exchanges. The client’s main concerns of headaches, difficulty sleeping, difficulty with memory and cognition, depression, anxiety, posttraumatic stress, anger, and chronic musculoskeletal pain were addressed and significantly improved within three weeks. The outcome of this case is promising and suggests that the highly individualized and collaborative interdisciplinary approach provided at MRIBH is particularly beneficial for veterans with chronic TBI and PTSD and can provide a roadmap for the treatment of specific clinical scenarios.